2022
DOI: 10.3390/ani12151897
|View full text |Cite
|
Sign up to set email alerts
|

Important Mycosis of Wildlife: Emphasis on Etiology, Epidemiology, Diagnosis, and Pathology—A Review: PART 2

Abstract: Wild animals are an important component of the ecosystem, and play a major role in it. However, in recent years, there has been an astronomical increase in the incidence of wildlife mycotic diseases leading to wildlife extermination. It is important to note that most of these mycotic diseases are zoonotic, and since there is a lot of attention given to zoonosis of a bacterial or viral origin in recent times, it is important to look into the mycotic diseases which may have zoonotic potential. Previously, the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 92 publications
0
0
0
Order By: Relevance
“…They are caused by microscopic fungi of three main genera— Trichophyton , Epidermophyton , Nannizzia , Paraphyton , Lophophyton , Microsporum , and Arthroderma. The study by Ugochukwu et al . (2022) has concluded that of the three genera of dermatomycoses, Epidermophyton affects exclusively humans, whereas Microsporum and Trichophyton , in most cases, affect animals.…”
Section: Introductionmentioning
confidence: 99%
“…They are caused by microscopic fungi of three main genera— Trichophyton , Epidermophyton , Nannizzia , Paraphyton , Lophophyton , Microsporum , and Arthroderma. The study by Ugochukwu et al . (2022) has concluded that of the three genera of dermatomycoses, Epidermophyton affects exclusively humans, whereas Microsporum and Trichophyton , in most cases, affect animals.…”
Section: Introductionmentioning
confidence: 99%